2022
DOI: 10.7759/cureus.27279
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Ventral Hernia Repair: Experience at a Tertiary Care Center in Western Rajasthan

Abstract: BackgroundVentral hernias are the second most common type of hernias accounting for 21-35% of all hernia types. Ventral hernia includes incisional, umbilical, epigastric, and Spigelian hernias, among others. Currently, patients and surgeons prefer laparoscopic repair of ventral hernias. This study aimed to compare laparoscopic with open hernia repair in terms of various operative and patient parameters. MethodologyThis was a prospective observational study conducted in the Department of General Surgery, Dr. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Murlidhar Kalyan and his colleagues [13] examined the differences and similarities between open and laparoscopic hernia repair in terms of a variety of operating and patient factors. They found that the mean operative time for the laparoscopic group was 57.52 minutes with a standard deviation of 5.80 minutes, while the mean operative time for the open group was 59.8 minutes with a standard deviation of 11.15 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Murlidhar Kalyan and his colleagues [13] examined the differences and similarities between open and laparoscopic hernia repair in terms of a variety of operating and patient factors. They found that the mean operative time for the laparoscopic group was 57.52 minutes with a standard deviation of 5.80 minutes, while the mean operative time for the open group was 59.8 minutes with a standard deviation of 11.15 minutes.…”
Section: Discussionmentioning
confidence: 99%